Genetic Control Of Natural Killing and In Vivo Tumor Elimination by the Chok Locus - Idris, Azza H. (The Rockefeller University Press, 1998)
The molecular mechanisms underlying target recognition during natural killing are not well understood. One approach to dissect the complexities of natural killer (NK) cell recognition is through exploitation of genetic differences among inbred mouse strains. In this study, we determined that interleukin 2–activated BALB/c-derived NK cells could not lyse Chinese hamster ovary (CHO) cells as efficiently as C57BL/6-derived NK cells, despite equivalent capacity to kill other targets. This strain-determined difference was also exhibited by freshly isolated NK cells, and was determined to be independent of host major histocompatibility haplotype. Furthermore, CHO killing did not correlate with expression of NK1.1 or 2B4 activation molecules. Genetic mapping studies revealed linkage between the locus influencing CHO killing, termed Chok, and loci encoded within the NK gene complex (NKC), suggesting that Chok encodes an NK cell receptor specific for CHO cells. In vivo assays recapitulated the in vitro data, and both studies determined that Chok regulates an NK perforin–dependent cytotoxic process. These results may have implications for the role of NK cells in xenograft rejection. Our genetic analysis suggests Chok is a single locus that affects NK cell–mediated cytotoxicity similar to other NKC loci that also regulate the complex activity of NK cells.